2013
DOI: 10.1111/j.1559-1816.2013.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the effectiveness of solution‐focused brief therapy and the quadripartite model of social competence and a fusion model of these two methods on increasing social adjustment of female students residing in Tehran dormitories

Abstract: The objective of this study is to compare the effectiveness of solution-focused brief therapy, the quadripartite model of social competence, and a fusion model of these two methods on increasing social competence of female students residing in Tehran dormitories. The studied sample includes 60 patients, randomly placed in three experimental groups and one control group. Analysis of covariance has been used to test the difference between group means. The results demonstrate that all three treatment methods were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Salary Feyzabad 60 reported that SFGC is effective in reducing mental pressure in high school student girls. The study by Saffarpoor et al 61 also showed that SFGC has had a significant effect in increasing the social compatibility of orphaned teens. The studies by Alimohammadi 62 and by Sarvi et al 63 indicate the efficiency of SFGC in promoting motivation, progress, and educational performance of the target group.…”
Section: Discussionmentioning
confidence: 93%
“…Salary Feyzabad 60 reported that SFGC is effective in reducing mental pressure in high school student girls. The study by Saffarpoor et al 61 also showed that SFGC has had a significant effect in increasing the social compatibility of orphaned teens. The studies by Alimohammadi 62 and by Sarvi et al 63 indicate the efficiency of SFGC in promoting motivation, progress, and educational performance of the target group.…”
Section: Discussionmentioning
confidence: 93%
“…In the last two years Google Scholar has identified over 1600 publications annually in many languages. Franklin et al (2011) describes the current research scene.…”
Section: Studies Of Outcome At the Present Datementioning
confidence: 99%
“…Social support is thought to be important in the adjustment process because it allows students to mobilize interpersonal resources to help them cope with the stress of adjusting to college (Compas et al, 1986). Previous research has suggested that students in their first year have more difficulty adjusting academically (Saffarpoor et al, 2011) however, if students can adapt themselves academically well, then all of their abilities will adjust to the college environment (Estiane, 2015). Based on of these findings, the most important thing for students in their first year of study is college adjustment.…”
Section: Introductionmentioning
confidence: 99%